Is Oral Communication Apprehension Reasonable?: A Study on Sociocultural Factors Among Indonesian EFL Learners - Al Awlaqi, Haifa Ali Salem Mansoor; Ghozali , Imam (REiLA : Journal of Research and Innovation in Language, 2023)
Globally, effective oral communication skills in English as a lingua franca have become increasingly important. However, many EFL learners, including those in Indonesia, experience apprehension about oral communication in culturally diverse environments. This study explores the phenomenon of oral communication apprehension among Indonesian EFL learners, focusing on identifying the sociocultural factors that hinder them. Using a single-case design, classroom observations, learner interviews, and a teacher focus group were conducted. Purposive sampling selected three ninth-grade students from selected private junior high school in Jember, who demonstrated apprehension in oral communication, and two EFL teachers experienced in addressing students' communication apprehension. Data analysis involved Ethnomethodological Conversation Analysis (ECA) and thematic coding. The findings indicate that factors like interruption, overlap, self-correction, self-monitoring, and reliance on the first language (L1) during oral communication contribute to apprehension. Additionally, sociocultural factors such as learners' attitudes, parental language background, language interference, and educational challenges were identified as contributing to oral communication apprehension among EFL learners. This study sheds light on the root causes of learners' struggles, encouraging them to overcome these challenges. It also offers valuable insights for educators to implement strategies that can alleviate the sociocultural burden faced by many EFL learners, especially relevant in Indonesia's context within the expanded circle of English language learning, where cultural nuances significantly influence language acquisition experiences.